Bipolar disorder and athletes: a narrative review - Daley, M. M.; Reardon, C. L. (Current Sports Medicine Reports, 2021)
Bipolar disorder is a diagnosis with immense lifelong implications that affects 1% to 2% of the general population. It typically presents during late adolescence and early adulthood, which often coincides with the age of peak athletic performance and a limited window of opportunity to compete at the highest levels of sport. Understanding the nature and course of the illness, as well as the effects that pharmacological treatment can have on an athlete, can be extremely beneficial for sports medicine physicians, particularly as many young athletes may not yet be diagnosed and/or adequately treated. Bipolar disorder is an incredibly complex and challenging diagnosis, but the ability to identify symptoms and intervene early is invaluable. The aim of this review is to summarize the available evidence and to highlight relevant risk factors, diagnostic features, management, and potential complications pertaining to the athletic population.